Virtualised and open RAN role in overhaul of mobile network sharing regulation in Europe for 5G rollout - Gábor Földes (International Telecommunications Society (ITS), 2023)
There is an investment gap to reach EU Digital Decade 2030 connectivity targets, requires from operators to provide full broadband fixed and mobile coverage. The reason is the lack of economies of scale, therefore return on investment often lags behind cost of capital in fragmented European national markets. Operators argue for market consolidation in form of horizontal merger, or at least market cooperation, like mobile network sharing. Operators accept horizontal production agreement network sharing as a second best solution, however the bottleneck is the regulatory approval of urban full (active and passive) radio access network (RAN) sharing. Regulators still insist on parallel infrastructure-based competition instead of service-based competition on the same infrastructure. Virtualisation and open RAN technology enablers of mobile 5G transform the industry from closed to open market organisations, where multivendor upstream market competition also strengthen operator downstream and end-user retail market competitions. The research question focused on how virtualized and open RAN with open market multivendor concept could mitigate regulatory anticompetitive concerns of network sharing in high density urban areas in end-user mobile services downstream market competition. The research methodology built on qualitative techniques due to new technology development and limited available data. Exploratory analysis covers relevant academic, research institutes and consultancy papers. Secondary market insight data used for market development analysis. The main finding is that, virtualised and open RAN intensifies competition, differentiation and innovation at vendor upstream market that has similar spillover effect to operator downstream and end-user retail markets. Due to network function virtualisation, software-based competition would permit higher economies of scale via network sharing at least in the physical hardware infrastructure segment, not only in passive, but also for active assets. The novelty of the paper to focus on the bottleneck of mobile network sharing approval in case of urban active RAN sharing and connects with open RAN as a potential mitigation opportunity to resolve regulatory uncertainty and promote an issue of new regulatory guidance on mobile network sharing, helping both operators and customers, resulting a social welfare increase.
Keywords: 330; network sharing; competition regulation; virtualisation; open RAN; 5G; cost efficiency; economies of scale